Genetic and metabolic characterization of individual differences in liver fat accumulation in Atlantic salmon - Horn, Siri S.; Sonesson, Anna K.; Krasnov, Aleksei; Aslam, Muhammad L.; Hillestad, Borghild; Ruyter, Bente (Frontiers in Genetics, 2025)
IntroductionLipid accumulation in the liver can negatively impact liver function and health, which is well-described for humans and other mammals, but relatively unexplored in Atlantic salmon. This study investigates the phenotypic, genetic, and transcriptomic variations related to individual differences in liver fat content within a group of slaughter-sized Atlantic salmon reared under the same conditions and fed the same feed. The objective was to increase the knowledge on liver fat deposition in farmed salmon and evaluate the potential for genetic improvement of this trait.MethodsThe study involved measuring liver fat content in a group of slaughter-sized Atlantic salmon. Genetic analysis included estimating heritability and conducting genome-wide association studies (GWAS) to identify quantitative trait loci (QTLs). Transcriptomic analysis was performed to link liver fat content to gene expression, focusing on genes involved in lipid metabolic processes.ResultsThere was a large variation in liver fat content, ranging from 3.6% to 18.8%, with frequent occurrences of high liver fat. Livers with higher levels of fat had higher proportions of the fatty acids 16:1 n-7, 18:2 n-6, and 18:1 n-9, and less of the long-chain omega-3 fatty acids. The heritability of liver fat was estimated at 0.38, and the genetic coefficient of variation was 20%, indicating substantial potential for selective breeding to reduce liver fat deposition in Atlantic salmon. Liver fat deposition appears to be a polygenic trait, with no large QTLs detected by GWAS. Gene expression analysis linked liver fat content to numerous genes involved in lipid metabolic processes, including key transcription factors such as LXR, SREBP1, and ChREBP.DiscussionThe results indicated a connection between liver fat and increased cholesterol synthesis in Atlantic salmon, with potentially harmful free cholesterol accumulation. Further, the gene expression results linked liver fat accumulation to reduced peroxisomal β-oxidation, increased conversion of carbohydrates to lipids, altered phospholipid synthesis, and possibly increased de novo lipogenesis. It is undetermined whether these outcomes are due to high fat levels or if they are caused by underlying metabolic differences that result in higher liver fat levels in certain individuals. Nonetheless, the results provide new insights into the metabolic profile of livers in fish with inherent differences in liver fat content.